2016
DOI: 10.18632/oncotarget.7325
|View full text |Cite
|
Sign up to set email alerts
|

Wip1 phosphatase: between p53 and MAPK kinases pathways

Abstract: Cells undergoing oncogenic transformation frequently inactivate tumor suppressor pathways that could prevent their uncontrolled growth. Among those pathways p53 and p38MAPK pathways play a critical role in regulation of cell cycle, senescence and cell death in response to activation of oncogenes, stress and DNA damage. Consequently, these two pathways are important in determining the sensitivity of tumor cells to anti-cancer treatment. Wild type p53-induced phosphatase, Wip1, is involved in governance of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 81 publications
0
47
0
Order By: Relevance
“…As a prominent modulator of the p53 system, Wip1 provides an entry point for crosstalk between the DNA damage response and other major signaling pathways. It has been reported that its expression levels are regulated by MAP kinase signaling [49], NF-κB activity [50] and the tumor suppressor HIPK2 [51].…”
Section: Discussionmentioning
confidence: 99%
“…As a prominent modulator of the p53 system, Wip1 provides an entry point for crosstalk between the DNA damage response and other major signaling pathways. It has been reported that its expression levels are regulated by MAP kinase signaling [49], NF-κB activity [50] and the tumor suppressor HIPK2 [51].…”
Section: Discussionmentioning
confidence: 99%
“…All these results further support the role of Wip1 in regulating tumorigenesis. Interestingly, Wip1 overexpression in mice does not lead to spontaneous tumor appearance (18), and Wip1 overexpression in the mammary gland epithelium is also not sufficient to induce cancer (2, 19). Therefore, Wip1 may actually not act as a cancer-initiating oncogene on its own but provides advantages for tumor development through its function on multiple target molecules.…”
Section: An Overview Of Phosphatase Wip1mentioning
confidence: 99%
“…These features are mainly connected with Wip1 ability to regulate DNA damage response (DDR) signaling and MAPK kinases pathway p53 network, including p38, p53, ATM, Chk2, and γ-H2AX [10,31,32]. Accumulating studies identified that high Wip1 expression disrupted the homeostasis maintained by the p38 MAPK-p53-Wip1 pathway, which caused downstream Wnt-p53 inactivation through p38 MAPK dephosphorylation, and promoted the development of malignant in humans by reducing p16 protein levels [33,34]. Our previous data have indicated that Wip1 is oncogenic and is involved in invasive growth in renal cancer cells and ICC cells [12,17].…”
Section: Discussionmentioning
confidence: 99%